Characterising Chinese Ru ware in the Sir Percival David collection at the British Museum using handheld XRF analysis - Delbey, Thomas; Harrison Hall, Jessica; Sheaf, Colin; Shortland, Andrew J. (Elsevier, 2022)
Ru ware is a very rare and highly prized stoneware from the end of the Northern Song period of China (960–1127 CE). Stylistic and art historical work by Regina Krahl (2021) suggests that a brush washer in the Sir Percival David Collection, housed in the British Museum, might be Ru rather than Korean Goryeo ware as previously thought. This paper reports the analysis of the glaze of this piece by handheld XRF in comparison with 10 pieces of Ru and 10 pieces of Goryeo ware. Despite the compositional similarity of the glazes, the analysis was able to show conclusively that the piece is Ru ware. The work has implications for the analysis of Chinese stoneware and beyond, showing that it may be possible (under the right conditions) to distinguish different productions relatively quickly and easily.
Keywords: China; Stoneware; Song Dynasty; Ru ware; Goryeo; Handheld XRF